Evolution of Community-Based Enterprise Governance Over Time: Lessons Learned from the Maya Biosphere Reserve - Megan Butler; Dean Current (Small-scale Forestry, 2022)

Scaling up of jujube-based agroforestry practice and management innovations for improving efficiency and profitability of land uses in Bangladesh - Ashim Kumar Das; Md. Abiar Rahman; Md. Mezanur Rahman; Satya Ranjan Saha; Sanjida Sultana Keya; Sumiya Surmin Suvoni; Md. Giashuddin Miah; Dean Current; Javed Rizvi (Agroforestry Systems, 2022)

Biophysical interactions in perennial biomass alley cropping systems - Joshua D. Gamble; Gregg Johnson; Dean A. Current; Donald L. Wyse; Diomides Zamora; Craig C. Sheaffer (Agroforestry Systems, 2019)

Impact of managed woodland grazing on forage quantity, quality and livestock performance: the potential for silvopasture in Central Minnesota, USA - Madeline M. Ford; Diomy S. Zamora; Dean Current; Joe Magner; Gary Wyatt; W. D. Walter; Sophia Vaughan (Agroforestry Systems, 2019)

Establishment and potential snow storage capacity of willow (Salix spp.) living snow fences in south-central Minnesota, USA - Eric J. Ogdahl; Diomy S. Zamora; Gregg Johnson; Gary Wyatt; Dean Current; Dan Gullickson (Agroforestry Systems, 2016)

Establishment and early productivity of perennial biomass alley cropping systems in Minnesota, USA - Joshua D. Gamble; Gregg Johnson; Craig C. Sheaffer; Dean A. Current; Donald L. Wyse (Agroforestry Systems, 2014)

Agroforestry - Diomides Zamora; Gary Wyatt; Dean Current; Dan Gullickson; David Smith; Joe Knights; Dinesh Paudel; Diomides Zamora; Gary Wyatt; Damion Drover; Rhett Jackson; Amy Grotta; et al. (Journal of Forestry, 2011)
375Blowing and drifting snow on Minnesota's roadways is a transportation efficiency and safety concern. Living snow fence is an agroforestry system involving planting of woody/tree species such as hybrid poplars, willow, other shrubs and pine trees along drifting snow areas. Establishing living snow fences improves driver visibility and road surface conditions and has the potential to lower costs of road maintenance, reduce accidents attributed to blowing and drifting snow, sequester carbon, and avoid the carbon emissions of snow removal operations. In recent years the Minnesota Department of Transportation (MNDOT) has paid farmers to leave standing corn rows to protect identified snow problem roadways. It also encourages farmers to plant living snow fences for such purpose but the adoption is too low. With increasing demand for corn to fuel the ethanol industry, paying $1.50 per bushel above market rate may not be sufficient incentive for leaving standing corn rows or to take land of production. With MNDOT's Memorandum of Understanding with USDA to plan living snow fences through the Conservation Reserve Program (CRP), now is an opportune time to review MNDOT's annual payment structure to farmers and prepare a new one. This project aims to 1) develop a calculator to estimate payments for farmers that will include considerations of safety and snow removal cost savings using living snow fence agroforestry systems; 2) work closely with MNDOT's engineers and plow operators to estimate the safety and snow removal costs and carbon emissions avoided through establishing living snow fences; and 3) evaluate farmers' willingness to establish snow fence and identify farmers/landowners constraints to adoption. This data will be provided to MNDOT to assist them in their decision making related to their living snow fence program, and data will be useful for other states wishing to address drifting snow problem areas using agroforestry systems.

Combining Biomass Harvest and Forest Fuel Reduction in the Superior National Forest, Minnesota - Michael C. Demchik; Dalia Abbas; Dean Current; Don Arnosti; Myra Theimer; Patty Johnson (Journal of Forestry, 2009)
Combining biomass harvest with forest fuel reduction may reduce the costs of fuel treatments. Our objectives were to determine the impact of combined biomass/fuel reduction harvests on the pools of forest fuels and to determine whether biomass harvest reduced the cost of mechanical fuel treatments. We tested two potential biomass harvest systems in wildland–urban interface areas with forest fuel accumulations on the Superior National Forest in Minnesota. Both systems performed similarly in terms of cost and efficiency at harvesting biomass. Overall, the cost of biomass harvest was impacted by site conditions, forwarding distance, the number of units harvested with one machine haul, the number of machines that were hauled, acres harvested, and inclusion of roundwood. Income from the sale of biomass did not cover the costs of harvest and delivery; however, for hauls of less than 100 mi, harvest may reduce the cost of the fuel reduction activity.

Moving agroforestry into the mainstream - Dean A. Current; Kenneth N. Brooks; Peter F. Ffolliott; Meagan Keefe (Agroforestry Systems, 2009)

Strategies for genetic conservation of trees in the Peruvian Amazon - Gregory A. O'Neill; Ian Dawson; Carmen Sotelo-Montes; Luigi Guarino; Manuel Guariguata; Dean Current; John C. Weber (Biodiversity and Conservation, 2001)